2009
DOI: 10.5012/bkcs.2009.30.11.2661
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of Nitrous Oxide by Slice Ion Imaging: The Stagnation Pressure Dependence

Abstract: Photodissociation of nitrous oxide near 203 nm has been studied by a combination of high resolution slice ion imaging technique and (2+1) resonance-enhanced multiphoton ionization (REMPI) spectroscopy of N2(X1Sg+) via the (a"'Zg+) state. We have measured the recoil velocity and angular distributions of N2 fragments by ion images of the state-resolved photofragments. The N2 fragments were highly rotationally excited and the NN-O bond dissociation energy was determined to be 3.635 eV Also, we investigated the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…18,19 The application of imaging techniques to cluster studies has been so far very limited and usually restricted to small species. 25) clusters. 23 There were only two recent studies, where also somewhat larger species were considered: e.g., pyrrole-ammonia 24 and N 2 O (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The application of imaging techniques to cluster studies has been so far very limited and usually restricted to small species. 25) clusters. 23 There were only two recent studies, where also somewhat larger species were considered: e.g., pyrrole-ammonia 24 and N 2 O (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The two data sets are in excellent agreement with one another, and with several other less extensive reports. 6,8,20 Both groups found that for N 2 (v = 0), β declines slowly with increasing j from β ∼ 1.0 at the low end of the rotational distribution near j = 60 to a value of about 0.7 at the peak of the rotational distribution near j = 78. It then declines more steeply, reaching β ∼ 0 at j = 89 near the high end of the rotational distribution.…”
Section: Introductionmentioning
confidence: 99%